The Reading Comprehension Skill of d/Deaf and Hard-of-hearing Poles and Its Importance for Media Accessibility: A Pilot Study - Aleksandrowicz, Pawel (Journal of Audiovisual Translation, 2019)
The study investigates the reading comprehension skill of d/Deaf and hard-of-hearing (DHH) Poles in the context of media accessibility. Deriving from the assumption that spoken Polish typically acts as a second language for the DHH, the study employed state certificate exams designed for foreigners learning Polish as a second language. A reading comprehension test was composed on the basis of these exams, containing tasks at B1, B2 and C1 proficiency levels. It was administered to 126 participants: 87 d/Deaf and hard-of-hearing (DHH) and 39 hearing persons acting as the control group. It was also accompanied by a demographic questionnaire to determine the relationship between the reading skill and such aspects as age, education, degree of hearing loss, onset of hearing loss, preferred means of communication (sign language, spoken Polish, both), declared proficiency in Polish and preferred media accessibility method (sign language interpretation, subtitling, either of the two).